Analisis Penerapan Metode Job Order Costing dalam Menghitung HPP dan Penentuan Harga Jual Produk pada Percetakan Bayu Aji - Shela Irvara Wulandari; Rifilia Ramadani; Aisyah Aisyah; Iskandar Iskandar; Hoirul Anam; Mochamad Reza Ardiyanto (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This study aims to evaluate the use of the job order costing method in calculating the cost of goods produced and determining the selling price of products at Bayu Aji Printing. This research uses a qualitative approach with a descriptive analysis method, which aims to present data systematically so as to facilitate understanding of the phenomenon and drawing conclusions. Data collection is done through direct observation and interviews with business owners. The results showed that Bayu Aji Printing has not implemented an appropriate calculation of the cost of goods produced which can affect the determination of product selling prices. Therefore, data analysis was carried out to calculate the cost of goods produced using the job order costing method to determine a more accurate selling price.